Penerapan Media Roda Buah Konkret Pengolahan Data untuk Meningkatkan Keaktifan Belajar Matematika Peserta Didik Kelas III SDN Banyuajuh 9 - Hidayat, Panji; Nabila, Sabrina Najwa; Pratama, Wahyu Pramudya; Rahmadani, Selviani; Khofifah, Vita (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
This classroom action research aimed to improve students’ participation in mathematics learning on data processing material through the use of the “Roda Buah” learning media in Grade III of SDN Banyuajuh 9. The low level of student participation, limited interaction, and difficulty in maintaining students’ focus during learning activities were identified as the main problems in this study. The research was conducted in two cycles, consisting of planning, action, observation, and reflection stages. The participants were 16 third-grade students. Data were collected through observation and documentation to measure students’ participation during the learning process. The results showed a gradual increase in student participation, from 37.5% in the preliminary condition, to 62.5% in Cycle I, and reaching 87.5% in Cycle II. These findings indicate that the implementation of the “Roda Buah” learning media created a more interactive and engaging learning environment, which encouraged students to be more actively involved in mathematics learning activities. This increased classroom engagement also provided a more conducive learning situation that supported students’ initial understanding of data processing concepts based on classroom learning experiences.
Keywords: Student Participation; Interactivelearning Media; Roda Buahan; Data Processing; Elementary School Mathematics